Effect of communication with electronic social media networking in emergency department of a rural tertiary care centre - Kumar, Anil; Singh, Somendra Pal; Gupta, Prashant; Gupta, Umesh; Gupta, Mohit; Singh, Praveen; Prakash, Manas (International Surgery Journal, 2016)
Background:Mode of communication in emergency is of prime importance when it comes to patient management or reporting of the patient. An expert opinion and timely information to senior consultants is to be always soughed whenever in doubt. A common electronic media platform can be very beneficial in such circumstances. Methods: All the residents and consultants of emergency team were connected on a common platform using WhatsApp and upload of information was done by residents on duty which was cleared by consultants. Results:A decrease in response time about diagnosis or management of patient was observed to be decreased along with more clear and visual information was available to seniors for their advice. A common platform for reporting and consultation was more appreciated among surgeons and Orthopedician. Conclusions:Using a common electronic platform for communication may be felt cumbersome with some amount of extra burden but definitely results into more accurate delivery of care to patients with in time expert opinion.